INTEGRATING TECHNOLOGICAL INNOVATION ACCEPTANCE AND DYNAMIC CAPABILITY PERSPECTIVES TO EXPLAIN E-COMMERCE USAGE BEHAVIOR - Amelia Amelia; M. Andri Radiany; Nuri Purwanto; Markus Prandini (Sampoerna University, 2026)
E-commerce usage behavior has become increasingly important in Indonesia as consumers continue to shift from conventional shopping to digital marketplace platforms. However, consumer usage of e-commerce cannot be explained only by platform availability, but also by how consumers evaluate technological innovation, customer value, platform capabilities, behavioral intention, and actual usage. This study examines e-commerce usage behavior by integrating the Acceptance of Technological Innovation Model and the Dynamic Capability perspective. Specifically, this research investigates the effects of perceived usefulness, perceived ease of use, and compatibility on customer value; the effects of customer value, market sensing capability, innovation capability, and customer relationship capability on behavioral intention toward e-commerce adoption; and the effect of behavioral intention on actual usage of e-commerce. This study also examines the mediating role of behavioral intention in the relationship between customer value, dynamic capability variables, and actual usage. A quantitative approach was adopted, with data collected through structured questionnaires from 150 respondents who had previously shopped through Shopee Mall Indonesia. The data were analyzed using SPSS, including validity and reliability tests, multiple regression analysis, t-tests, F-tests, and Sobel tests. The results indicate that perceived usefulness, perceived ease of use, and compatibility have positive and significant effects on customer value. Customer value, innovation capability, and customer relationship capability significantly influence behavioral intention, while market sensing capability does not have a significant effect. Behavioral intention has a positive and significant effect on actual usage and mediates the effects of customer value, innovation capability, and customer relationship capability on actual usage. However, behavioral intention does not mediate the relationship between market sensing capability and actual usage. Hence, the study recommends that e-commerce platforms should strengthen customer value, service innovation, and customer relationship capability to increase behavioral intention and sustain actual usage.